2020
DOI: 10.7705/biomedica.5802
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 y RT-PCR en pacientes asintomáticos: resultados de una cohorte de trabajadores del Aeropuerto Internacional El Dorado de Bogotá, 2020

Abstract: Introducción. La pandemia de COVID-19 ha ocasionado cerca de 25 millones de casos en el mundo. Se ha descrito que los pacientes asintomáticos pueden ser fuentes de transmisión. Sin embargo, es difícil detectarlos y no es claro su papel en la dinámica de transmisión del virus, lo que obstaculiza la implementación de estrategias para la prevención.Objetivo. Describir el comportamiento de la infección asintomática por SARS-CoV-2 en una cohorte de trabajadores del Aeropuerto Internacional El Dorado “Luis Carlos Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Nineteen of the PCR-based studies collected data on symptoms longitudinally after testing, making it possible to distinguish between presymptomatic and asymptomatic infection ( 15 , 17 , 18 , 20 , 22 , 25 , 26 , 27 , 32 , 37–40 , 45 , 47 , 48 , 51 , 53 , 54 ). The follow-up period in these studies ranged from 2 to 70 days, with a median of 14 days (IQR, 14.0 to 15.8 days).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen of the PCR-based studies collected data on symptoms longitudinally after testing, making it possible to distinguish between presymptomatic and asymptomatic infection ( 15 , 17 , 18 , 20 , 22 , 25 , 26 , 27 , 32 , 37–40 , 45 , 47 , 48 , 51 , 53 , 54 ). The follow-up period in these studies ranged from 2 to 70 days, with a median of 14 days (IQR, 14.0 to 15.8 days).…”
Section: Resultsmentioning
confidence: 99%
“… 28 During a cohort of 202 Colombian workers, C t values in asymptomatic patients did not differ significantly from the symptomatic ones, the mean C t value in the asymptomatic group were 33.53 for ORF1ab gene and 33.61 for N gene, C t value in the symptomatic group was 34.13 for ORF1ab . 29 , 30 In contrast, a study regarding viral dynamics in 31 asymptomatic COVID‐19 patients showed that 22 presented symptoms after their hospital admission and that their C t values ( C t = 39) previously were significantly higher than those of symptomatic patients ( C t = 34.5). 30 In the present study, we found that patients with COVID‐19 exhibited higher C t values than AHW, similarly to C t values described by Kim et al, 27 but in our study, positive AHW were not presymptomatic subjects since they never exhibited symptoms related to COVID‐19.…”
Section: Discussionmentioning
confidence: 95%
“… 29 , 30 In contrast, a study regarding viral dynamics in 31 asymptomatic COVID‐19 patients showed that 22 presented symptoms after their hospital admission and that their C t values ( C t = 39) previously were significantly higher than those of symptomatic patients ( C t = 34.5). 30 In the present study, we found that patients with COVID‐19 exhibited higher C t values than AHW, similarly to C t values described by Kim et al, 27 but in our study, positive AHW were not presymptomatic subjects since they never exhibited symptoms related to COVID‐19.…”
Section: Discussionmentioning
confidence: 95%
“…As we found in another study of a relatively small group of HIV/SARS-CoV-2 co-infected people, the maximum of T cell response to SARS-CoV-2 acute infection is usually observed since Day 6 to 16 34 . As well, PaO 2 /FiO 2 ratio was measured on Days 8–12 (1) to correspond roughly with T cell measurements; and (2) since it was demonstrated by different groups of researchers that severe COVID-19-associated ARDS is generally detected after the first week of the COVID-19 disease 35 38 . Two separate intakes and two separate measurements with calculating the average value were made in every analysis, to reduce the contribution of experimental errors.…”
Section: Methodsmentioning
confidence: 70%